Synthesis and characterization of a nanogel encapsulating Silicon Quantum Dots (SIQDS) for enhanced targeted photodynamic therapy in HeLa cancer cells - Ponce Bohorquez, Ariana Fernanda (2024)
The prevalence of cancer remains a major health issue globally. Current treatments, such as chemotherapy and radiation, often result in severe side effects due to their non-selective nature. As an alternative, targeted photodynamic therapy (PDT) has emerged as a promising solution due to its specificity and reduced systemic toxicity. However, challenges such as solubility and stability in biological media need to be addressed to enhance efficacy. This research aims to develop and assess a novel nanogel system for encapsulating two types of SiQDs—Acid-SiQDs and Acid-PEO-SiQDs—and to evaluate their efficacy in targeted photodynamic therapy against HeLa cells. The nanogels were synthesized using a copolymer matrix of Di(ethylene glycol) methyl ether methacrylate (DEGMA) and 2-Methacryloyloxyethyl phosphorylcholine (MPC) via reversible addition-fragmentation chain transfer (RAFT) polymerization. The biocompatibility of these nanogels was assessed in Human Dermal Fibroblasts, adult (HDFa) cells using the MTT (3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide) assay to evaluate cell viability post-exposure. Additionally, the effectiveness of the PDT was tested against HeLa cells under controlled near-infrared radiation to initiate the photodynamic effect. The synthesized nanogels demonstrated high biocompatibility, maintaining cell viability above 80% at various concentrations when tested in fibroblast cultures. In photodynamic therapy applications, the encapsulated SiQDs, especially the Acid-PEO-SiQDs (SiQDs OX), showed significant potential in inducing cytotoxicity in HeLa cells, confirming the targeted action of the therapy. The thermoresponsive behavior of the nanogels, driven by DEGMA, played a significant role in enhancing their stability at physiological temperature (37°C).